Comparative Analysis of Islamic Education Policies in Indonesia and Russia - Usman, Errina; Hunaida, Wiwin Luqna; Mala, Asnal; Irwanto, Moch. Surya Hakim; Muhid, Abdul (Letiges, 2024)
This research discusses Islamic education policies in Indonesia and Russia. The importance of this study is based on the Islamic education policy process in countries with a majority Muslim population and countries with a majority non-Muslim population. This research was conducted using a qualitative approach, and data was collected from books, journals and experts' thoughts related to the research theme. Data was obtained with the help of an electronic database site with a Scopus-indexed national and international journal search site, which was then mapped by searching for inclusive and exclusive criteria. The next step was selecting studies, collecting data, and extracting data, and the data was analyzed using comparative techniques. Based on the findings, Islamic education policies have been implemented in Indonesia and Russia, as evidenced by the policies issued by the government for implementing Islamic education from the lowest level of education to the highest level of education. Indonesia implements an integral curriculum policy combining religious and general education. Russia implements a mandatory curriculum policy that requires students to choose their religious education, including Islamic education. Through this research, it is known that there is still room for Islamic education in secular countries, and secular countries believe that Islamic education plays a vital role in creating a generation of character. Thus, this research significantly contributes to the development of Islamic education at the global level by identifying space for Islamic education in secular countries and emphasizing the critical role of Islamic religious education in creating a society with character. This enriches discussions about the relationship between religion and education in the context of multiculturalism and religious pluralism and provides a basis for developing inclusive and sustainable education policies in various countries.